Proof of principle: Transformation approach alters caudate nucleus volume and structure-function associations. - Schwab, Nadine; Tanner, Jared; Nguyen, Peter; Schmalfuss, Ilona; Bowers, Dawn; Okun, Michael; Price, Catherine; Schwab, Nadine A; Tanner, Jared J; Nguyen, Peter T; Schmalfuss, Ilona M; Price, Catherine C (Brain Imaging & Behavior, 2015)
Brain magnetic resonance image (MRI) registration alters structure orientation, size, and/or shape. To determine whether linear registration methods (image transformation to 6, 9, and 12° of freedom) alter structural volume and cognitive associations, we examined transformation alterations to the caudate nucleus within individuals diagnosed with Parkinson's disease (PD) and demographically matched non-PD peers. Volumes from native and six were expected be significantly different from 9 and 12° of freedom methods. Caudate nucleus volumes were expected to be associated with measures of processing speed and mental flexibility, but the strength of the association based on transformation approach was unknown. MRI brain scans from individuals with Parkinson's disease (n = 40) and age-matched controls (n = 40) were transformed using 6, 9, and 12° of freedom to an average brain template. Correlations controlling for total intracranial volume assessed expected structural-behavioral associations. Volumetric: Raw 9 and 12° transformed volumes were significantly larger than native and 6° volumes. Only 9 and 12° volumes revealed group differences with PD less than controls. Intracranial volume considerations were essential for native and 6° between group comparisons. Structural-Behavioral: The 9 and 12° caudate nucleus volume transformations revealed the expected brain-behavioral associations. Linear registration techniques alter volumetric and cognitive-structure associations. The study highlights the need to communicate transformation approach and group intracranial volume considerations.